2020
DOI: 10.15376/biores.15.1.1510-1520
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy and greenhouse gas emissions of rice straw to energy chain in Egypt

Abstract: Rice straw as a source of energy could substitute for fossil fuels and reduce greenhouse gas (GHG) emissions. Thus, the aim of this paper was to analyze the energy and GHG emissions of rice straw to the energy chain in Egypt. The analysis was performed starting from paddy production, straw collection and transportation, and energy generation for two scenarios: power plant and anaerobic digestion plant. The results showed that the paddy production and transportation stage represented the highest contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Pyrolysis is a thermal treatment of medical wastes in the absence of oxygen, which can produce gaseous and liquid products that can be used as a source of chemicals and fuels ( Som et al, 2018 ). Anaerobic digestion is an environmentally friendly technique used for biochemical treatment of wastes and produce biogas that can be used for heat and power generation ( Abdel Daiem et al, 2018 ; Said et al, 2020 ). Furthermore, renewable energies from solar, wind and biomass can also meet the energy requirements of waste treatment technique and mitigate greenhouse gas emissions generated from fossil fuel consumption for energy generation ( Said et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrolysis is a thermal treatment of medical wastes in the absence of oxygen, which can produce gaseous and liquid products that can be used as a source of chemicals and fuels ( Som et al, 2018 ). Anaerobic digestion is an environmentally friendly technique used for biochemical treatment of wastes and produce biogas that can be used for heat and power generation ( Abdel Daiem et al, 2018 ; Said et al, 2020 ). Furthermore, renewable energies from solar, wind and biomass can also meet the energy requirements of waste treatment technique and mitigate greenhouse gas emissions generated from fossil fuel consumption for energy generation ( Said et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic digestion is an environmentally friendly technique used for biochemical treatment of wastes and produce biogas that can be used for heat and power generation ( Abdel Daiem et al, 2018 ; Said et al, 2020 ). Furthermore, renewable energies from solar, wind and biomass can also meet the energy requirements of waste treatment technique and mitigate greenhouse gas emissions generated from fossil fuel consumption for energy generation ( Said et al, 2020 ). This can support decision-makers in developing strategies for the sustainability by using the eco-friendly and economic technologies for efficient medical waste treatment that can be implemented in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the European Commission put forward an initiative to achieve net-zero emissions by 2050 [8]. The Commission called for studying the sustainability of They reported that the energy consumption of straw collection ranged between 1.73 and 2.52 MJ/kg [46]. Shang et al [48] used the same methodology as Said et al [46].…”
Section: Introductionmentioning
confidence: 99%
“…The Commission called for studying the sustainability of They reported that the energy consumption of straw collection ranged between 1.73 and 2.52 MJ/kg [46]. Shang et al [48] used the same methodology as Said et al [46]. However, a product (grain) and a byproduct (straw) have different energy equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…About 1 to 1.5 megagrams of rice straw are produced for every megagram of paddy [2][3][4]. In many rice-growing countries, the most common rice straw waste 2 of 18 management method is open-field burning [5][6][7][8][9][10][11]. In the Philippines, farmers turn to open-field burning to drive away pests and to avoid the labor-intensive, manual gathering of rice straw [2,7].…”
Section: Introductionmentioning
confidence: 99%